Strategi Komunikasi Dakwah Da’i Hidayatullah dalam Membina Masyarakat Pedesaan - Bustanol Arifin (Communicatus: Jurnal Ilmu komunikasi, 2018)
This paper aims to determine the da'i Hidayatullah da'wah communication strategy in fostering rural communities which are formulated into three questions as follows: the role of da'i Hidayatullah in raising awareness of rural communities. The diffusion of da'i Hidayatullah's da'wah communication in fostering rural communities and the innovation of da'i Hidayatullah's da'wah communication in fostering rural communities in Cimenyan district, Bandung regency. The research method uses descriptive methods by making the da'i Hidayatullah Bandung district that fosters rural communities as the main source of this research. This type of research is qualitative. The results showed that the Hidayatullah preacher had a role as a change agent by conducting persuasive-informative communication in raising and fostering rural communities in the Cimenyan sub-district, Bandung regency. The diffusion of da'wah communication carried out by Hidayatullah in developing rural communities in the Cimenyan district of Bandung district through activities in the form of majelis ta'lim, grand MBA, training of bina aqidah, qur'an education park (TPA) and mosque youth in which da'wah messages in the form of aqeedah, shari'ah, and morals. Da'i Hidayatullah's innovation in da'wah communication was in the form of implementing an empowerment program which included empowering human resources (HR) and the community economy which was formed through training and recitation activities.Tulisan ini bertujuan untuk mengetahui strategi komunikasi dakwah da’i Hidayatullah dalam membina masyarakat pedesaan yang dirumuskan menjadi tiga pertanyaan  sebagai berikut: peran da’i Hidayatullah dalam menyadarkan masyarakat pedesaan. Difusi komunikasi dakwah da’i Hidayatullah dalam membina masyarakat pedesaan dan inovasi komunikasi dakwah da’i Hidayatullah dalam membina masyarakat pedesaan di kecamatan Cimenyan kabupaten Bandung. Metode penelitian menggunakan metode deskriptif dengan menjadikan da’i Hidayatullah kabupaten Bandung yang membina masyarakat pedesaan sebagai sumber utama dalam penelitian ini. Jenis penelitian adalah kualitatif. Hasil penelitian menunjukkan bahwa da’i Hidayatullah berperan sebagai agen perubah dengan melakukan komunikasi persuasif-informatif dalam menyadarkan dan membina masyarakat pedesaan di kecamatan Cimenyan kabupaten Bandung. Difusi komunikasi dakwah yang dilakukan oleh da’i Hidayatullah dalam membina masyarakat pedesaan di kecamatan Cimenyan kabupaten Bandung melalui kegiatan berupa majelis ta’lim, grand MBA, training bina aqidah, taman pendidikan al-qur’an (TPA) dan remaja masjid yang didalamnya disampaikan pesan-pesan dakwah berupa pesan aqidah, syari’ah, dan akhlak. Inovasi komunikasi dakwah yang dilakukan oleh da’i Hidayatullah berupa penyelenggaraan program pemberdayaan yang meliputi pemberdayaan sumber daya manusia (SDM) dan ekonomi masyarakat yang dibentuk melalui kegiatan pelatihan dan pengajian.